Pelaksanaan Program Wajib Belajar Pendidikan Dasar Sembilan Tahun pada Pondok Pesantren Salafiyah IBNU Taimiyyah Kebokura Sumpiuh Banyumas - Rifqi Abdul Rosyad (Institut Agama Islam Negeri Purwokerto, 2019)
Abstract This paper focused describing the implementation of the Nine-Year Compulsory Basic Education Learning Program at the Salafiyyah Ibn Taimiyah Islamic Boarding School in Kebokura, Sumpiuh, Banyumas Regency in terms of the Director General Decree of Islamic Institution Number: E / 239 / 2001. This is a qualitative research the subjects of which are the caregivers of Islamic boarding schools, Muslim scholars, Administrative Staff (TU), and santri. The data of this research were collected through observation, interviews and documentation. The results showed that the Implementation of the Nine-Year Compulsory Basic Education Study Program at Ibn Taymiyyah Islamic Boarding School was good, because of the 11 criteria contained in the Director General of Islamic Institutional Decree Number: E / 239/2001 concerning the implementation of the Compulsory Education Program in this institution is appropriate. In addition, the implications of the implementation of the Nine-Year Compulsory Basic Education Learning Program at Ibn Taymiyyah Islamic Boarding School had many positive impacts on management, such as the admission of certificate equivalece to formal education, the integration of religious and general education, the increase number of santri and regular funding from the government.. Keywords program implementation, nine-year basic education compulsory education program at salafiyah islamic boarding school, director general of islamic religion decision number: E/239/2001 Abstrak Tulisan ini bermaksud untuk menguraikan pelaksanaan program Wajib Belajar Pendidikan Dasar Sembilan Tahun di Pondok Pesantren Salafiyyah Ibnu Taimiyah Kebokura Sumpiuh Banyumas ditinjau dari Keputusan Direktur Jenderal Kelembagaan Agama Islam Nomor: E / 239 / 2001. Jenis penelitian yang digunakan dalam penelitian ini adalah penelitian kualitatif, subjek penelitiannya adalah pengasuh pondok pesantren, Ustadz dan Staff Tata Usaha (TU) serta santri. Teknik yang digunakan dalam pengumpulan datanya adalah observasi, wawancara dan dokumentasi. Hasil penelitian menunjukan bahwa Pelaksanaan Program Wajib Belajar Pendidikan Dasar Sembilan Tahun di Pondok Pesantren Salafiyah Ibnu Taimiyah baik, karena dari 11 kriteria yang terdapat dalam Keputusan Direktur Jenderal Kelembagaan Agama Islam Nomor: E / 239 / 2001 tentang penyelenggaraan Program Wajib Belajar Pendidikan Dasar pada Pondok Pesantren salafiyah Pondok Pesantren Salafiyah Ibnu Taimiyah sudah sesuai. Kemudian implikasi diterapkannya Program Wajib Belajar Pendidikan Dasar Sembilan Tahun di Pondok Pesantren Salafiyah Ibnu Taimiyah memberikan banyak dampak positif terhadap manajemen di Pondok pesantren tersebut, mulai dari ijazah pondok yang setara dengan pendidikan formal, integrasi pendidikan agama dan umum, peningkatan jumlah santri dan adanya sumber dana yang sudah pasti dari pemeintah.